Beyond spatial and temporal averages: ecological responses to extreme events may be exacerbated by local disturbances. Issue 1 (December 2015) - Ghedini, Giulia; Russell, Bayden; Falkenberg, Laura; Connell, Sean
Abstract Background The ecological consequences of climate change will be driven by a combination of both gradual and abrupt changes in climatic conditions. Despite growing evidence that abrupt abiotic change of extreme events may profoundly alter ecological processes, it remains unclear how such events may combine with longer-term global and local disturbances. Here, we focused on a key process of herbivory and tested how its strength would change in response to forecasted global (CO2 enrichment) and local disturbances (nutrient enrichment) under abrupt (heat wave) or gradual (future temperature) changes in temperature, using an herbivorous gastropod and turf algae interaction within kelp forests as a model system. Results The heat wave caused the greatest magnitude of change in consumption across all treatment combinations. The positive effect of nutrient enrichment on consumption was magnified by increasing temperature, but caused surprisingly intense herbivory when combined with the heat wave. Carbon and nutrient enrichments individually increased consumption with nitrogen overriding the positive effects of CO2 . Conclusions These results not only reveal that the strength of ecological responses to extreme events may substantially exceed those manifested under 'average' future conditions, but also that the effects of extremes may be exacerbated by local disturbances. If disproportionate ecological change occurs where extreme events overlap with local disturbances, scientists and managers will need to recognize spatial and temporal heterogeneities of environmental change to think beyond averages.